Pre-partition India and the Rise of Indian Nationalism in Amitav Ghosh’s 'The Shadow Lines' (English Department, Faculty of Languages and Arts, Universitas Negeri Semarang, 2020)
The Shadow Lines is mostly celebrated for capturing the agony and trauma of the artificial segregation that divided the Indian subcontinent in 1947. However, the novel also provides a great insight into the undivided Indian subcontinent during the British colonial period. Moreover, the novel aptly captures the rise of Indian nationalism and the struggle against the British colonial rule through the revolutionary movements. Such image of pre-partition India is extremely important because the picture of an undivided India is what we need in order to compare the scenario of pre-partition India with that of a postcolonial India divided into two countries, and later into three with the independence of Bangladesh in 1971. This paper explores how The Shadow Lines captures colonial India and the rise of Indian nationalism through the lens of postcolonialism.